Altruism and Patience in Choices between Financial Losses – Experimental Findings - Karbowski, Adam; Wiśnicki, Bartłomiej (Altruizm i cierpliwość w wyborach w kontekście strat finansowych – wnioski z eksperymentu, 2023)
In this empirical study (n = 102), the authors set out to investigate the relation between altruism (measured with the use of individual social discounting rates) and patience (measured with the use of delays) under the conditions of financial losses. Thanks to the titration algorithm by Holt et al. (2003), and the Area Under the Curve indicator by Myerson et al. (2001), the study could apply discounting procedures to assess the altruism and patience of individuals. It was found that altruism and patience can be but do not have to be positively correlated in the domain of economic losses. It turns out that the occurrence of a positive correlation between altruism and patience (as often reported in the behavioural economics literature devoted to economic gains) depends on the temporal structure of the discounting task (temporal context of choice). When both the loss for the decision maker and another person from the social distance scale is delayed (shifted in time), positive correlations between altruism and patience are not observed. The latter finding is novel and nuances the behavioural economics knowledge on the relation between altruism and patience in economic choices.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 1, s. 64-78
Keywords: altruism; patience; delay discounting; social discounting; behavioural economics; altruizm; cierpliwość; dyskontowanie w czasie; dyskontowanie społeczne; ekonomia behawioralna